Increasing Cropping Intensity and Crop Productivity of Four Crops Based Mustard-Boro-T. Aus-T. Aman Cropping Pattern - Barman, A; Shome, S; Khatun, MR; Masud, MM; Akther, S (Bangladesh Agronomy Journal, 2021)
A field trial on soil test based (STB) fertilizer doses was conducted during the year of 2017-2018 and 2018-2019 in Jashore region (AEZ-11) to find out the most suitable fertilizer doses for four crop based cropping pattern considering the agronomic feasibility and economic return of the system. The experiment consisted of eight different treatments viz. T1: 100% NPKSZnB (STB), T2: T1 + 25% N, T3: T1 + 25% NP, T4: T1 + 25% NK, T5:T1 + 25% PK, T6:T1 + 25% NPK, T7: 75% of T1, T8: Native fertility. Randomized complete block design (RCBD) with three replications was followed. Data revealed that seed yield of mustard was remarkably influenced by fertilizer treatments while grain yield of other components of the cropping system was not affected significantly by the treatments except control or native fertility. It was observed that 25% more NPK over 100% STB dose provided the highest yield of all the component crops. The highest rice equivalent yield (3.34 t ha-1) was recorded from T6 and the lowest (1.88 t ha-1) from T8 treatment. Maximum gross return (Tk. 420000/ha) and marginal benefit cost ratio (4.08) were also obtained from T6 treatment. So, 25% NPK+ 100% STB dose of fertilizer could be followed for productive and remunerative rice based cropping system Mustard-Boro-T. Aus-T.Aman in AEZ-11. Bangladesh Agron. J. 2021, 24(1): 109-117